Job Enjoyment in High-Risk Job: A Study on Window Cleaners - Ziherlan, Oby; Arifianto, Chandra (Journal of Business Management and Economic Development, 2025)
This study aims to examine the phenomenon of job enjoyment among window cleaners at PT ISS Indonesia, located in South Jakarta. This qualitative research adopts a case study approach, involving six window cleaners as informants and one supervisor as a key informant to provide additional insights into job enjoyment. Data were collected through observation, interviews, and documentation and analyzed using data triangulation. The findings indicate that several factors influence employees’ job enjoyment, including the level of enjoyment experienced, structured training programs, a positive job environment, and flexible job hours, all of which impact employees’ decisions to stay or switch jobs. Additionally, mood and workplace challenges serve as motivational factors, encompassing personal interests, the nature of the job itself, and the sense of fulfillment or achievement. The study reveals that while most employees enjoy their jobs, some do not fully experience job satisfaction within their role or job environment.